2012
DOI: 10.1111/j.1365-2672.2012.05237.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tet gene and complete genome sequencing of tet gene-encoded plasmid (pAHH01) isolated from Aeromonas species in South Korea

Abstract: Aims:  To investigate the tetracycline resistance related to tet genes in Aeromonas isolates collected from water and diseased fish in South Korea. Methods and Results:  A total of 34 Aeromonas strains were examined for their susceptibility to tetracycline using the minimum inhibitory concentration (MIC) assay, and the genetic determinants (tetA to E) were analysed. Among these strains, the tetA and tetE genes were predominant (tetA was found in six strains, and tetE was found in nine strains), and 15 strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Our study showed that tetracycline resistance of Aeromonas spp. isolates from common carp was encoded mostly by the tet(E) gene which has been previously shown to be a dominant tetracycline resistance gene in aeromonads from fresh fish aquaculture (Nawaz et al 2006;Cizek et al 2010;Han et al 2012). Two isolates resistant to tetracycline that were negative for tet genes likely carry one of the less frequent tetracycline resistance determinants that were not tested in our study (Akinbowale et al 2006).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our study showed that tetracycline resistance of Aeromonas spp. isolates from common carp was encoded mostly by the tet(E) gene which has been previously shown to be a dominant tetracycline resistance gene in aeromonads from fresh fish aquaculture (Nawaz et al 2006;Cizek et al 2010;Han et al 2012). Two isolates resistant to tetracycline that were negative for tet genes likely carry one of the less frequent tetracycline resistance determinants that were not tested in our study (Akinbowale et al 2006).…”
Section: Discussionmentioning
confidence: 65%
“…; Han et al . ). Two isolates resistant to tetracycline that were negative for tet genes likely carry one of the less frequent tetracycline resistance determinants that were not tested in our study (Akinbowale et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the frequently occurring BHR plasmids that were discussed earlier (IncA/C, IncU, IncQ), plasmids belonging to IncFrepB, IncFIB, IncFIC and IncI groups were also observed in the genus Aeromona s (Han et al, 2012b ; Moura et al, 2012 ; Maravić et al, 2013 ). The study of Maravić et al ( 2013 ) found 40-kb conjugative plasmids described as narrow host range IncFIB group in 11 A. caviae strains isolated from Croatian mussels.…”
Section: Mobile Genetic Elements and Mechanisms Of Horizontal Gene Trmentioning
confidence: 92%
“…These results are in concordance with the taxonomic assignments of the plasmid-containing host bacteria from the BPS as determined by 16S rRNA gene sequencing 14 . Some of the reference plasmids encoding the identified Rep proteins, such as pCAR1 19 , pND6-1 20 , pSTY 21 , and pDK1 22 contain degradative genes, and others such as pMET-1 23 , RP4 24 , pAHH01 25 , pIE321 26 , and pTB11 27 contain antibiotic resistance genes. Identity values between the identified Rep proteins and the best BLASTp hit in the NCBI database ranged from 46% to 100% ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%